Chloroplast genome of silverleaf nightshade (Solanum elaeagnifolium Cav.), a Weed of National Significance in Australia - Zhu, Xiaocheng (Mitochondrial DNA B Resour, 2020)
Solanum elaeagnifolium Cav. is a widely distributed weed and recognized as a Weed of National Significance in Australia. This study sequenced the chloroplast (cp) genome of S. elaeagnifolium, which is 155,049 bp in length, including a large single-copy region at 85, 426 bp, a small single-copy region at 18,419 bp and two inverted repeats at 25,602 bp. A total of 130 genes were annotated. The phylogeny among the S. elaeagnifolium and 42 Solanum chloroplast genomes suggested S. elaeagnifolium is closely related to Solanum species from the section of Melongena.